A compendious review on clay modification techniques for wastewater remediation - PATANJALI, POOJA; CHOPRA, INDU; PATANJALI, NEERAJ; SINGH, RAJEEV (The Indian Journal of Agricultural Sciences, 2021)
Presence of significant quantities of toxic dyes has led to contamination of fresh water resources. The limited availability of fresh water has escalated the pressure on maintaining sustainable agricultural production to ensure food security. So , there is a need to recycle the wastewater and to explore the possibility to reuse it for irrigation purpose. Amongst different techniques, adsorption has been found to be the best way for the remediation of colored effluents. The concept of recycling and reuse of wastewater has propelled the exploration of potential inexpensive adsorbents. Clays are cheap, non-toxic abundantly available natural materials. Over the recent years, researchers have focused on clays modification to enhance their adsorption efficiency for the remediation of contaminants such as dyes from wastewater. Therefore, the present article is written with an aim to systematically summarize the recent advancements in clay modification and their potential as effective adsorbing agents for the removal of various dyes from contaminated wastewaters. A detailed description of various clay modification techniques such as treatment with surfactant, acid, heat, plasma, polymer, silane, metal oxide has been presented here. The effect of various physicochemical process parameters such as solution pH, initial dye concentration, adsorbent dosage and temperature on the performance of modified clays has also been presented. Based upon the final outcome of literature review, it can be concluded that modified clays are much better adsorbing agents in comparison to the natural clays. Hence, modified clays represent an economically viable and sustainable option for the purification of wastewaters containing dyes and it can be utilized for irrigating different crops at the places where fresh water resources have either depleted or limited.